2019
DOI: 10.1177/0263617419878541
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tectonic deformation on coal methane adsorption capacity

Abstract: Tectonic deformation can cause significant changes in the physical and chemical structures of coal by damaging the macrostructure and macromolecular composition. For thorough research on the coal tectonic deformation impacts on gas adsorption capacity, this paper collected and summarized the parameters of experimental adsorption isotherms and coal macerals, conducted proximate and ultimate analyses, and systematically discussed the adsorption properties of different structures of coals and the influence of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Zhao et al. (2019) and Li (2015) obtained the adsorption capacity of the primary structure coal and tectonic coal by a WY-98A gas adsorption constant analyzer at a temperature of 303 K, as shown in Figure 14. As shown in Figure 14, the adsorption quantity increases with increasing adsorption equilibrium pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al. (2019) and Li (2015) obtained the adsorption capacity of the primary structure coal and tectonic coal by a WY-98A gas adsorption constant analyzer at a temperature of 303 K, as shown in Figure 14. As shown in Figure 14, the adsorption quantity increases with increasing adsorption equilibrium pressure.…”
Section: Resultsmentioning
confidence: 99%
“…He et al [11] made a comparative analysis on the difference of adsorption isotherms of CH 4 , H 2 S and N 2 , and concluded that the adsorption capacity of each gas increases with the increasing of pressure and van der Waals force when the pressure is less than 10 MPa. Li et al [12] founded that tectonic deformation have an impact on CH 4 adsorption in coal. Deng et al [13] believed that gas extraction in high-gas coal mines rich in sulfur change the gas partial pressure in coal seams, thus producing hydrogen sul de gas.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the research on the complex and exclusive characteristics of tectonic coal not only establishes the basic theory of geological body structure and tectonic changes under the action of geotectonic movement, but also plays an important guiding role in engineering practice such as coal seam outburst risk prediction and underground gas drainage in CBM low-permeability enrichment areas (Pan et al, 2012;Li et al, 2019;Zhang et al, 2022). Based on the long-term research and knowledge in structural composition of organic matter in tectonic coal and coal-methane adsorption through the author's research group (Huan et al, 2015;Zhang et al, 2018;Wang et al, 2021a;Yang et al, 2021), this paper summarizes and prospects the progress made in the study of methane adsorption capacity and behavior of tectonic coal in recent years, hoping to share and communicate, and promote further research on the adsorption of tectonic coal, so as to provide a reference for the prediction and prevention of gas disasters in outburst coal seam and to improve the recovery ratio of coal seam methane.…”
Section: Introductionmentioning
confidence: 99%